A GEVP formulation for robust predictor feedback controller design of linear systems with uncertain input delay. Issue 5 (4th April 2022) - Huang, Chao; Zhang, Linlin; Zhang, Changzhu; Zhang, Hao
Abstract : Predictor feedback controllers are irreplaceable and widely used for systems with long input delays. However, it is also known to be sensitive to mismatch between the nominal input delay and the true unknown one. In this paper, we propose a robust predictor feedback controller design to enlarge the admissible delay mismatch, while keeping the convergence rate within a prescribed level. It is shown that the controller synthesis problem can be cast into a generalised eigenvalue problem (GEVP).